Pelatihan Sterilisasi Alat Dan Bahan Medis Pada Anggota Tim Bantuan Medis Vertebrae Fakultas Kedokteran Universitas Pattimura - Eka Astuty; Ony Wibriono Angkejaya (Edumedia Solution, 2022)
The Vertebrae Medical Assistance Team (TBM) of the Faculty of Medicine, University of Pattimura is a student organization that has many work programs, and one of their work programs is community service. Medical students will become doctors who will take part in society and who are not only required to be capable and competent in solving all health problems, but also must be able to become examples and role models in moving healthy life for the community. As part of the TBM, medical students are required to have basic medical assistance competencies, therefore, the purpose of this activity is to provide detailed knowledge of sterilization and disinfection techniques that have been neglected so far, starting with simple basic knowledge. In general, the implementation methods used in this community service are sterilization education, sterilization objectives, types of sterilization, and the practice of using autoclave sterilizers. This community service activity has achieved the main planned objectives, namely increasing the knowledge and understanding of participants through sterilization training for medical equipment and materials as part of the program to increase the competence of TBM members. There are three main components discussed in the understanding and skills of participants, namely understanding the definition and purpose of sterilization, understanding the types of sterilization, and being able to practice how to use autoclave sterilizers